Prevalence of tinnitus and hearing loss in South African dentists and investigation into possible connections with noise levels and frequencies in the dental environment - Sidley, Clive Graham (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2004.